Application of Dexmedetomidine Sedation Combined With Suprascapular Nerve Block and Axillary Nerve Block in Shoulder Arthroscopy, A Randomized Single-Blind Study - Chu-Ting Wang; Liang-Ming Zhu; Ji-Ling Wu; Fen-Fen Kang; Zhi-Jian Lin (Frontiers Media S.A., 2021)
Objective: The aim of the present study was to evaluate the anesthetic and analgesic effects of dexmedetomidine combined with suprascapular nerve block and axillary nerve block in shoulder arthroscopy.Methods: A total of 60 patients were randomly divided into the experimental group (DEX group) and the control group (GA group) via a random number table method. Dexmedetomidine sedation combined with suprascapular nerve block and axillary nerve block was used in the DEX group, while general anesthesia with tracheal intubation combined with interscalene brachial plexus block was used in the GA group. The perioperative indexes, intraoperative hemodynamics, cerebral oxygen saturation, and postoperative pain score, as well as any complications, were compared between the two groups.Results: The anesthesia duration (p < 0.05) and postoperative monitoring time (p < 0.05) in the DEX group were significantly shorter than those in the GA group. At most time points during the anesthesia, the cerebral oxygen saturation (p < 0.05) and mean arterial pressure (p < 0.05) in the DEX group were significantly higher than those in the GA group. Additionally, the decrease in the cerebral oxygen saturation and mean arterial pressure in the GA group was significantly higher than that in the DEX group (p < 0.05). The pain score of DEX group 12 h after operation significantly lower than that in the GA group (p < 0.05), and the incidence of postoperative hypoxemia along with nausea and vomiting in the GA group was significantly higher than that in the DEX group (p < 0.05).Conclusion: Dexmedetomidine combined with suprascapular nerve block and axillary nerve block could reduce the incidence of hypoxemia, while the approach demonstrated better hemodynamic stability, fully ensured the cerebral blood perfusion, and exhibited better anesthetic and analgesic effects, meaning it could be safely and effectively applied in shoulder arthroscopy procedures.